2020
DOI: 10.1002/cncr.33348
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life outcomes among breast cancer survivors

Abstract: Background Data from a nationwide sample of US breast cancer survivors were used to examine associations between patient characteristics (breast cancer clinical features, prognostic factors, and treatments) and health‐related quality of life (HRQOL). Associations between postdiagnosis HRQOL and mortality were then evaluated. Methods The authors identified female breast cancer survivors (n = 2453) from the Sister Study or Two Sister Study who were at least 1 year from breast cancer diagnosis and who had respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…An interesting finding was that for our analyses, number of comorbidities and QoL were not related. This is in direct contrast to much of the breast cancer survivorship literature [33,34]. However, previous literature has focused on younger or all aged BCS rather than older BCS.…”
Section: Discussionmentioning
confidence: 87%
“…An interesting finding was that for our analyses, number of comorbidities and QoL were not related. This is in direct contrast to much of the breast cancer survivorship literature [33,34]. However, previous literature has focused on younger or all aged BCS rather than older BCS.…”
Section: Discussionmentioning
confidence: 87%
“…Prior research has also found that comorbid conditions can have a negative impact on health related QOL [ 28 31 ]. A recent prospective cohort study from the United States found that five years after breast cancer diagnosis, reporting one or more comorbid condition was associated with worse health related QOL scores [ 29 ]. Importantly, the study also concluded that poor health related QOL scores, were associated with a significantly increased hazard of all cause mortality [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective cohort study from the United States found that five years after breast cancer diagnosis, reporting one or more comorbid condition was associated with worse health related QOL scores [ 29 ]. Importantly, the study also concluded that poor health related QOL scores, were associated with a significantly increased hazard of all cause mortality [ 29 ]. Similarly, among breast cancer patients receiving chemotherapy, having a greater number of comorbid conditions has also been associated with poorer physical and role functioning, greater pain, worse sleep quality, and fatigue [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting nding was that for our analyses, number of comorbidities and QoL were not related. This is in direct contrast to much of the breast cancer survivorship literature [33,34]. However, previous literature has focused on younger or all aged BCS rather than older BCS.…”
Section: Discussionmentioning
confidence: 87%